TO EVALUATE THE ANTI-ATHEROSCLEROTIC POTENTIAL OF QUERCETIN IN ALLOXANINDUCED DIABETIC RATS FED WITH HIGH-FAT DIET - S, Biplav; G, Sindhura; Gowda K P, Shivalinge (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The main aim of the present study is concerned with the evaluation of anti-atherosclerotic potential of quercetin in alloxan-induced diabetic rats fed with high-fat diet (HFD). Methods: Atherosclerosis (AS) is the major cause for many of the cardiovascular disease, and it is accelerated in the presence of diabetes mellitus and causes profound alterations in the lipid profile. The method used for the induction of AS was using HFD for 60 days. In this study, rats were divided into four groups (n=6). Group I served as normal control, Group II alloxan (120 mg/kg b.w i.p)-treated diabetic rats, Group III received quercetin (50 mg/ kg b.w p.o), and Group IV received atorvastatin (10 mg/kg b.w p.o) along with alloxan (120 mg/kg b.w i.p) on the 1st day of the days of the study period. AS was induced in Group II, Group III, and Group IV rats by feeding them with HFD from the 1st day to 60th day. The body weight, feed intake was measured daily. The blood was withdrawn from retro-orbital plexus, and the serum was used for the estimation of lipid profile (total cholesterol [TC], triglycerides [TGs], low-density lipoprotein cholesterol [LDL-C], very LDL-C [VLDL-C], and high-density lipoprotein cholesterol [HDL-C]). After scarification under overdose of ketamine, the histopathological study of aorta was carried out. Results: The results showed that the quercetin-treated rats showed a decrease in body weight gain, decreased levels of TC, TGs, LDL-C, and VLDL-C, and increased levels of HDL-C were observed in Group III rats when compared to alloxan-induced diabetic rats fed with HFD (Group III). The histopathological study of aorta showed no development of plaques and of foam cells. Conclusion: From this study, it can be calculated that quercetin has anti-atherosclerotic activity as it significantly altered overall lipid profile in diabetic rats fed with HFD. This activity may be attributed to its antioxidant, inhibition of HMG-CoA reductase activity of quercetin.